1981
DOI: 10.1073/pnas.78.6.3328
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of two divergent rat genomic clones homologous to the transforming gene of Harvey murine sarcoma virus.

Abstract: Harvey murine sarcoma virus (Ha-MuSV) is a mouse-rat recombinant retrovirus that encodes a protein designated p21, required for virally induced transformation. Using a radiolabeled DNA fragment from the p21 coding region, we have detected homologous DNA sequences in the normal DNA of rats and of several other vertebrate species. Moreover, many tested cells from these species contain low levels of a p21 protein that is highly related to viral 21. Now we report two independent fragments from normal rat DNA conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
89
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 270 publications
(95 citation statements)
references
References 36 publications
6
89
0
Order By: Relevance
“…Blair et al first demonstrated that the mouse mos proto-oncogene can transform NIH 3T3 cells when placed under the control of retroviral regulatory elements (6). Similar results have subsequently been obtained with other proto-oncogenes such as H-ras-J (7,9) and sis (8,12).…”
supporting
confidence: 62%
“…Blair et al first demonstrated that the mouse mos proto-oncogene can transform NIH 3T3 cells when placed under the control of retroviral regulatory elements (6). Similar results have subsequently been obtained with other proto-oncogenes such as H-ras-J (7,9) and sis (8,12).…”
supporting
confidence: 62%
“…These subtle changes are sufficient to confer transforming properties to the ras proteins (16,25,31). There is evidence that a substantial increase in normal rcas p21 expression can be transforming as well (1).…”
mentioning
confidence: 98%
“…This truncated EGR receptor is constitutively active, and therefore cells expressing v-erb undergo a chronic EGF stimulation (Lax et al, 1985). An example of a viral oncogene coding for a critical component of growth signal transduction pathways is represented by Ha-MuSV (homologue to the cellular gene Ha-ras) (DeFeo et al, 1981), encoded by the Harvey murine sarcoma virus. An example of a viral oncogene encoding a transcription factor is provided by REV-T, homologous to a member of the NFkB protein family (Wilhelmsen et al, 1984;Lee et al, 1991), encoded by the Reticuloendotheliosis virus.…”
Section: Gain Of Function In the Pathway Of Malignant Transformation:mentioning
confidence: 99%